Accuracy of a Clinical Applicable Method for Prediction of VO2max Using Seismocardiography - Hansen, Mikkel Thunestvedt; Husted, Karina Louise Skov; Fogelstrøm, Mathilde; Rømer, Tue; Schmidt, Samuel Emil; Sørensen, Kasper; Helge, Jørn (International Journal of Sports Medicine, 2023)
Cardiorespiratory fitness measured as ˙VO2max is considered an important variable in the risk prediction of cardiovascular disease and all-cause mortality. Non-exercise ˙VO2max prediction models are applicable, but lack accuracy. Here a model for the prediction of ˙VO2max using seismocardiography (SCG) was investigated. 97 healthy participants (18–65 yrs., 51 females) underwent measurement of SCG at rest in the supine position combined with demographic data to predict ˙VO2max before performing a graded exercise test (GET) on a cycle ergometer for determination of ˙VO2max using pulmonary gas exchange measurements for comparison. Accuracy assessment revealed no significant difference between SCG and GET ˙VO2max (mean±95% CI; 38.3±1.6 and 39.3±1.6 ml·min−1·kg−1, respectively. P=0.075). Further, a Pearson correlation of r=0.73, a standard error of estimate (SEE) of 5.9 ml·min−1·kg−1, and a coefficient of variation (CV) of 8±1% were found. The SCG ˙VO2max showed higher accuracy, than the non-exercise model based on the FRIENDS study, when this was applied to the present population (bias=−3.7±1.3 ml·min−1·kg−1, p<0.0001. r=0.70. SEE=7.4 ml·min−1·kg−1, and CV=12±2%). The SCG ˙VO2max prediction model is an accurate method for the determination of ˙VO2max in a healthy adult population. However, further investigation on the validity and reliability of the SCG ˙VO2max prediction model in different populations is needed for consideration of clinical applicability.
Keywords: maximal oxygen consumption; ˙VO2max prediction; test accuracy